Portrayal of Dissociative Identity Disorder Experienced by The Main Character in “Glass” (2019) Movie - Shaney Auryn Putri Aziza; Robby Satria (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This research uses a descriptive qualitative method to analyze the depiction of dissociative identity disorder (DID) experienced by Kevin in the film “Glass”. The purpose of this study is to examine whether Kevin’s portrayal of DID is in accordance with the diagnostic criteria stated by American Psychiatric Association (2013) in its book entitled